2011
DOI: 10.3758/s13423-011-0172-z
|View full text |Cite
|
Sign up to set email alerts
|

Entirely irrelevant distractors can capture and captivate attention

Abstract: The question of whether a stimulus onset may capture attention when it is entirely irrelevant to the task and even in the absence of any attentional settings for abrupt onset or any dynamic changes has been highly controversial. In the present study, we designed a novel irrelevant capture task to address this question. Participants engaged in a continuous task making sequential forced choice (letter or digit) responses to each item in an alphanumeric matrix that remained on screen throughout many responses. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 18 publications
3
41
0
1
Order By: Relevance
“…Many studies have examined performance regarding unattended stimuli (e.g., [37], [38], [39]). The responses to the unattended conversation in this study were stronger than those in some studies [34], [39], [40].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined performance regarding unattended stimuli (e.g., [37], [38], [39]). The responses to the unattended conversation in this study were stronger than those in some studies [34], [39], [40].…”
Section: Discussionmentioning
confidence: 99%
“…A recent series of studies by Forster and Lavie (2008a,b, 2011) (see Figure 1C) introduced a new measure designed to meet these criteria. These studies have demonstrated robust RT slowing in the presence, versus absence, of a colorful distractor image (e.g., of the cartoon character Spiderman) across two different task types: a letter search (Forster and Lavie, 2008a,b) and a sequential forced-choice response task (Forster and Lavie, 2011; Figure 2).…”
Section: Irrelevant Distraction: External Sourcesmentioning
confidence: 99%
“…A recent series of studies by Forster and Lavie (2008a,b, 2011) (see Figure 1C) introduced a new measure designed to meet these criteria. These studies have demonstrated robust RT slowing in the presence, versus absence, of a colorful distractor image (e.g., of the cartoon character Spiderman) across two different task types: a letter search (Forster and Lavie, 2008a,b) and a sequential forced-choice response task (Forster and Lavie, 2011; Figure 2). Irrelevant distractor interference has been found for meaningless (a colorful shape) and frequently presented (50% trials) stimuli, but was greater for semantically meaningful (e.g., a famous cartoon character) and infrequently presented (10% trials) stimuli (Forster and Lavie, 2008b, see also Biggs et al, 2012 for further examination of effects of meaningfulness on irrelevant distraction).…”
Section: Irrelevant Distraction: External Sourcesmentioning
confidence: 99%
“…However, when participants could not anticipate the presence of a face (as in Experiments 1a/b), an extended attentional dwell on the faces could not be avoided. Of note, and unlike previous studies of distraction (e.g., Forster & Lavie, 2011), our study isolated the holding of attention by the presence of a distractor stimulus from attentional effects triggered by the offset of that stimulus. By using a relatively long stimulus duration (4 s), we ensured that the abrupt offset of the stimulus, which can automatically capture attention in a manner similar to an abrupt onset (Miller, 1989), would be unlikely to interfere with our measure of attentional dwell time.…”
Section: Discussionmentioning
confidence: 82%